(untitled) (Journal of Hama University, 2021)
This study aimed to detect the prevelance of toxoplasmosis in women and sheep in Hama city by using Indirect Latex Agglutination Test, and finding factors related infection in women and sheep, where this study was conducted on (100) random samples for women in Hama in the northern , southern and eastern countryside, aged between 61-18 years old , were sampling during months of January and February 2020 and a questionnaire was prepared for collecting all their information. Also (100) samples have been collected of (14) different groups of aborted sheep located in al mazarb and eastern areas of Hama during the period of October, November and December from 2019. The results of this study showed that the prevelance of women in Hama city was /56% /, Samples were divided into four age groups and the prevelance of women aged 30-18 was / 45.83% / and those aged between 40-31 were /58.06%/, Prevelance of the 50-41 age group is/ 58.33%/ and between the age of 61-51 was /61.90%/. The prevalence by location distributed accordingly in Hama city was /37.5%/ , in the Eastern region was (68.96%), in the southern region was /47.61%/ while in the northern region it was /65.38%/ . The infection rate in sheep was / 67%/ in the eastern region and the Mazarb region, while the infection rate among sheep raised in the eastern region by a sorority breeding system was 91.11% , and The incidence of sheep in the Mazarb area with half-open breeding was /47.27%/ . From this study , we conclude that the age, place of residence, and contact with animals in women has a significant impact on the prevelance of infections , and that sheep raised in flocks have a higher incidence of infection than sheep raised in semi-open sheds.